2021
DOI: 10.3390/healthcare9111438
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Exercise on Irisin Blood Levels—Systematic Review and Meta-Analysis

Abstract: Physical exercise may activate a number of important biochemical processes in the human body. The aim of this systematic review and meta-analysis was to identify the long-term effect of physical activity on irisin blood levels. We searched PubMed, Scopus, and Web of Science for articles addressing the long-term effect of physical exercise on irisin blood levels. Fifty-nine articles were included in the final qualitative and quantitative syntheses. A statistically significant within-group effect of exercise on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 86 publications
1
19
0
1
Order By: Relevance
“…On the other hand, although the discoveries about myokine irisin are promising in the peripheral and central fields, many questions have to be resolved. The meta-analysis aimed to identify the long-term effect of physical activity on blood levels and detailed that among 33 studies, the level increased into circulation 23x and decreased 10x ( Jandova et al, 2021 ). The meta-analysis reviewed that physical exercise increases irisin blood levels.…”
Section: The Neuroprotective Potential Of Exerkinesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, although the discoveries about myokine irisin are promising in the peripheral and central fields, many questions have to be resolved. The meta-analysis aimed to identify the long-term effect of physical activity on blood levels and detailed that among 33 studies, the level increased into circulation 23x and decreased 10x ( Jandova et al, 2021 ). The meta-analysis reviewed that physical exercise increases irisin blood levels.…”
Section: The Neuroprotective Potential Of Exerkinesmentioning
confidence: 99%
“…However, the long-term effect depends on the type of physical exercise. Overall results so far are still limited and more research on the effects of different types of exercise and exercise protocols on peripheral and central levels of irisin will importantly contribute to the understanding of the roles of irisin in health and disease ( Albrecht et al, 2020 ; Jandova et al, 2021 ).…”
Section: The Neuroprotective Potential Of Exerkinesmentioning
confidence: 99%
“…A recent systematic review and meta-analysis in 2021 compared the effect of exercise on irisin blood levels in 33 studies (Briken et al, 2016), with increased levels of irisin in 23 of these studies and decreased in another 10, with rather inconsistent results in individual studies. In the reported literature, exercises that have caused a decrease in irisin serum levels have included high-intensity circuit training (Yang et al, 2019), mixed physical training (Jandova et al, 2021), periodic sprint training (Gmiat et al, 2017), indoor aerobic training (Murawska-Cialowicz et al, 2015), and high-altitude mountaineering (Ozbay et al, 2020). Furthermore, even in the studies that have reported post-exercise upregulation of irisin, the timing of irisin upregulation is not same.…”
Section: E Ects Of DI Erent Types Of Exercise On Irisinmentioning
confidence: 99%
“…Jandova ve ark. [29] kandan irisin ölçümünde kullanılan ticari ELISA kitlerindeki poliklonal antikorlarla (pAb'ler), insan ve hayvan serumlarındaki spesifik olmayan proteinlerin çapraz reaksiyona girerek hatalı ölçümler yapılabileceğini belirtmişlerdir. Bu yayında, egzersizin kan irisin seviyesine etkisi üzerine yapılan çalışmaların sonuçlarının değerlendirildiği meta-analize göre; antrenmanın türü ne olursa olsun egzersiz etkisiyle irisin artışının istatistiksel olarak anlamlı bulunduğu bildirilmiştir [29].…”
Section: Serum İrisin Düzeylerinin Elisa Yöntemi Ile öLçümüunclassified